1988
DOI: 10.1152/jappl.1988.64.2.585
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex function in endurance- and static exercise-trained men

Abstract: The effect of exercise training mode on reflex cardiovascular control was studied in a cross-sectional design. We examined the cardiovascular responses to progressive incremental phenylephrine (PE) infusion to maximal rates of 120 micrograms/min and the delta heart rate/delta blood pressure responses to lower body negative pressure (LBNP) to -50 Torr in 30 men who were either endurance exercise trained (ET), untrained (UT), or weight trained (WT). During PE infusion, measures of blood pressures, forearm blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 0 publications
4
32
0
3
Order By: Relevance
“…In addition, there may be a ceiling for maximal vagal activity and vagal effects on the heart may be greatest in young adult humans and may not be able to be enhanced. Both cross-sectional (Smith et al, 1988) and longitudinal data (Kingwell et al, 1992) suggest that cardiac vagal baroreflex control is not enhanced by endurance training in young individuals. In contrast, our prior work showed that baroreflex gain is preserved in older active individuals and this was achieved primarily through enhanced neural control (Hunt et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, there may be a ceiling for maximal vagal activity and vagal effects on the heart may be greatest in young adult humans and may not be able to be enhanced. Both cross-sectional (Smith et al, 1988) and longitudinal data (Kingwell et al, 1992) suggest that cardiac vagal baroreflex control is not enhanced by endurance training in young individuals. In contrast, our prior work showed that baroreflex gain is preserved in older active individuals and this was achieved primarily through enhanced neural control (Hunt et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding this finding, Levine and colleagues (Levine et al 1991;Levine, 1993) suggested that endurance training induced cardiac remodelling; greater ventricular diastolic chamber compliance and distensibility on the steeper part of the Frank-Starling cardiac function curve may be a mechanical, non-autonomic cause of orthostatic intolerance. In addition, an attenuation of arterial baroreflex function is a contributory factor for the increased predisposition to orthostatic hypotension in endurance-trained individuals (Raven et al 1984;Smith et al 1988;Stevens et al 1992;Ogoh et al 2003). Likewise, Cooper & Hainsworth (2002) demonstrated that patients with posturally related syncope fail to enhance carotid baroreflex sensitivity during orthostatic stress.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic cardiovascular regulatory system is exquisitely adapted for maintaining an adequate cerebral circulation to prevent syncope (Raven et al 1984;Smith et al 1988;Stevens et al 1992;Cooper & Hainsworth, 2001, 2002Ogoh et al 2003), but the contribution of the systemic cardiovascular regulatory system to orthostatic tolerance is unknown. Another considerable physiological factor that determines orthostatic tolerance is cerebral blood flow (CBF) or its regulation, because CBF is reduced immediately after orthostatic stimulation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the normal condition, EX increases cardiac vagal tone and reduces sympathetic outflow at rest (8,12,21). On the other hand, variable changes in arterial baroreflex sensitivity (BRS) have been reported to be reduced (32,43,49,51) in subjects after a course of EX. Few data exist on the role of EX in the modulation of neurohumoral function in CHF.…”
mentioning
confidence: 99%